2013
DOI: 10.1136/gutjnl-2013-305386
|View full text |Cite
|
Sign up to set email alerts
|

β7 integrins are required to give rise to intestinal mononuclear phagocytes with tolerogenic potential

Abstract: Mice lacking β7 integrins in the innate immune compartment are more susceptible to intestinal inflammation, which is correlated with a requirement of β7 integrins to reconstitute gut mononuclear phagocytes with tolerogenic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
2
31
1
Order By: Relevance
“…37 Using T-cell transfer model of chronic colitis, Villablanca et al 37 showed that T cell-mediated colitis was aggravated in Itgb7 À / À Rag2 À / À mice compared with Rag2 À / À mice because of the impaired homing of mononuclear phagocytes to the gut, indicating a protective role of mononuclear phagocytes in chronic colitis. Taken together, mononuclear phagocytes might have distinct roles in inflammatory response in the gut under different conditions.…”
Section: Discussionmentioning
confidence: 98%
“…37 Using T-cell transfer model of chronic colitis, Villablanca et al 37 showed that T cell-mediated colitis was aggravated in Itgb7 À / À Rag2 À / À mice compared with Rag2 À / À mice because of the impaired homing of mononuclear phagocytes to the gut, indicating a protective role of mononuclear phagocytes in chronic colitis. Taken together, mononuclear phagocytes might have distinct roles in inflammatory response in the gut under different conditions.…”
Section: Discussionmentioning
confidence: 98%
“…2 The vitamin A metabolite retinoic acid (RA), produced by CD103 DCs via the enzyme retinaldehyde dehydrogenase 2 (encoded by Aldh1a2 gene), acting on T cells plays a critical role in this intestinal imprinting, 3 and DCs with this capacity can be identified by an assay that detects this enzymatic activity (ALDE + ). 4 Pharmacological intervention in tissuespecific recruitment of T cells has the potential advantage of very precise therapeutic intervention at the site of inflammation. 5 This theoretical promise that stemmed from fundamental work and preclinical model systems was indeed upheld.…”
mentioning
confidence: 99%
“…A paper by Mora and colleagues elegantly highlights that α 4 β 7 integrins have important roles in innate immune cells as well, and that α 4 β 7 is required to mediate an important tolerogenic function of the mucosal immune system. 4 While blockade of α 4 β 7 integrin in immunodeficient, lymphopenic mice transferred with CD45RB high T cells has previously been shown to prevent colitis, 12 transfer of CD45RB high T cells into hosts that genetically lack β 7 integrin surprisingly accelerated colitis, 4 implying a protective role of this gut-homing integrin in the innate immune system. Notably, in a series of elegant competitive reconstitution experiments, the authors demonstrated that β 7 expression on bone marrow precursors was required to locate tolerogenic CD11c DCs, identified by their capacity to metabolise vitamin A as identified by the ALDEfluor assay, in Peyer's patches, small intestinal lamina propria and mesenteric lymph nodes, but β 7 was surprisingly not required for colonic DC reconstitution.…”
mentioning
confidence: 99%
See 2 more Smart Citations